The impact of mental health and psychological stressors on menstrual cycle modulation: exploring the influence of age and hormonal contraceptives - Petrine, Jéssica Pereira Castro; Jacques, Larissa Sampaio; da Cruz Santos, Tayná Márcia; Pereira, Fernanda Aparecida Castro; Castelo, Paula Midori; -Borges, Bruno Del Bianco (Archives of women's mental health, 2025)
Stress, infections, and psychological and social well-being can affect the reproductive system. Activation of the hypothalamic-pituitary-adrenal axis can disrupt ovarian cyclicity. Estrogens can modulate stress responsiveness and mood. Thus, understanding this interaction and how it modulates the menstrual cycle is crucial for women’s reproductive health. Purpose The objective of this study was to analyze the influence of a stressor, a period of the Covid-19 pandemic when there were no vaccines available yet, on the psychological state of women aged 18 to 45 years; as well as the influence of mental health on the menstrual cycle, considering the influence of age and hormonal contraceptives. Method Online questionnaire using the Google Forms platform was used. Results There is a high prevalence of the onset of new psychosocial symptoms. Moreover, most women reported some type of change in their menstrual cycles. The women who were using hormonal contraceptives demonstrated a higher frequency of spotting and menstrual color alterations, while women without hormonal contraceptives demonstrated a higher frequency of cycle duration and menstrual odor alterations. Women without hormonal contraceptives were more susceptible to the development of psychosocial symptoms. Younger adult women were more affected by menstrual changes and psychosocial symptoms. Close to 90% of women who reported several psychosocial symptoms had changes in their menstrual cycles. Conclusion These data suggest the impact of stressors, such as a period of the pandemic, on mental health and menstrual cycles, and younger adult women can be more susceptible. This reflects the relationship between mental and reproductive health.